Battery Energy Storage Station Based Smoothing Control of Wind and Photovoltaic Power Generation Fluctuations Using SOC Control Strategy - John, Dayana.V.; Marsaline Beno, D. M. (Asian Journal of Electrical Sciences, 2014)
The battery energy storage system (BESS) is the current typical means of smoothing intermittent wind or solar power generation. Such BESS hybrid power systems require a suitable control strategy that can effectively regulate power output levels and battery state of charge (SOC). This paper presents the results of a wind/PV/BESS hybrid power system simulation analysis under taken to improve the smoothing performance of wind and Photovoltaic (PV) power generation and the effectiveness of battery SOC control. A wavelet based power smoothing method is presented for reducing output power fluctuations of wind/PV hybrid power generation systems and regulating the battery SOC. The effectiveness of the proposed method was verified using MATLAB/SIMULINK software.